The impact of cultural value contents on the development and shaping of international criminal law - Ristivojević Branislav (Zbornik Radova: Pravni Fakultet u Novom Sadu, 2011)
The paper discusses the relationship between the cultural value contents on shaping and development of international criminal law. It was established long time ago that the response of each society to the criminality is closely connected with its value basis. Which society values will be protected by the criminal law and from which attacks depends on people value judgment on what is good and what is bad. Since the cultures around the world differ the value systems also differ. For this reason the international legislator developed long tradition of difficult harmonization of value judgments so that its provisions become acceptable for great number of states. This leads to the number of insufficiently regulated, amorphous and fluid definitions in the international law and constant rejection by its enteritis to obey to the imperative provisions of this law. Each attempt to deviate from this tradition is the reason for loosing efficiency, which is proved by the author through the failure of imperative institutes of the international criminal law like for example ad hoc tribunals. The conclusion would be that domestic, and not the international, criminal proceedings are always more efficient type of criminal justice. The author is of the opinion that dominant religious ethics is the main factor that is shaping value judgments of certain culture. The author claims that due to the major religious diversities between the cultures it is not possible to carry out entire value harmonization in the international arena. Today the majority of authors in the field of international criminal law will agree that establishment of this type of law is described as 'pro-western oriented' in different cultures of the world. This conclusion is best proved if one takes into consideration the small, almost insignificant support of the International Criminal Tribunal out of the 'western civilization'. The further consequence of the value disharmony suffered by the international law is that there is no full and complete policy for repressing international crime. Between the two possible paths the author prefers to harmonize international criminal justice with cultural diversities that burden it than to adopt one cultural or value pattern. In contrary, the international criminal law would be considered and evaluated by its addressees as one of the mechanisms for imposing the system of values by the politically and economically more powerful culture.